2020
DOI: 10.1021/acscatal.9b05604
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of the PET Film by MHETase Using Exo-PETase Function

Abstract: Monohydroxyethyl terephthalate (MHET) hydrolase (MHE-Tase) is an enzyme known to be involved in the final degradation step of poly(ethylene terephthalate) (PET) by hydrolyzing MHET into terephthalic acid and ethylene glycol in Ideonella sakaiensis. Here, we report the extracellular production of MHETase in an active form with a proper folding. Based on the structural observations and biochemical experiments, we reveal that MHETase also functions as exo-PETase by hydrolyzing the synthesized PET pentamer. We fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
85
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 26 publications
2
85
0
1
Order By: Relevance
“…A similar Ca 2+ binding site was characterized for Aspergillus oryzae FaeB ( Ao FaeB), wherein it was hypothesized to have a role in stabilizing the lid domain ( 38 ). Overall, the structure of MHETase is most similar to that of FAEs, as discussed previously ( 35 , 36 ). The structural conservation between the hydrolase domains of MHETase and PETase is striking ( Fig.…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…A similar Ca 2+ binding site was characterized for Aspergillus oryzae FaeB ( Ao FaeB), wherein it was hypothesized to have a role in stabilizing the lid domain ( 38 ). Overall, the structure of MHETase is most similar to that of FAEs, as discussed previously ( 35 , 36 ). The structural conservation between the hydrolase domains of MHETase and PETase is striking ( Fig.…”
Section: Resultssupporting
confidence: 72%
“…The enzyme kinetics studies presented here reveal a substantial reduction in activity for the S131G, E226T, and F495I MHETase mutants, indicating that these positions play important roles in substrate specificity and catalytic efficiency. A previous study also demonstrated greatly reduced hydrolytic activity by a F415S variant ( 36 ). Additionally, two homologs identified via bioinformatics analysis from C. thiooxydans and Hydrogenophaga sp.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Without immediate interventions in plastic usage and industrial-scale changes to the intended life cycle of plastics, plastic consumption is projected to grow 300% between 2014 and 2050 3 . To address this exponentially growing crisis, researchers have begun to turn attention towards enzymebased strategies for recycling and bioremediation [4][5][6][7][8][9] . Careful kinetic studies must be performed to identify accurate structure-function relationships for plastic-hydrolase engineering, but analyses of the initial phases of the reactions are not commonly reported, sometimes leading to misinterpretation of effects of mutations.…”
mentioning
confidence: 99%